IMPLEMENTASI KURIKULUM MERDEKA DI MIN 12 MEDAN - Sakinah Hasbi; Aufa, Cahya Widiya Putri, Elisa Febriyanti, Mas Bulan Harahap, Nadia Haviza Purba (CV. ADIBA AISHA AMIRA, 2024)
This research aims to explore teachers' views and experiences regarding the implementation of the Independent Curriculum in schools. The research method used was qualitative with an in-depth interview approach to teachers. The research results show several main findings: 1). Teachers stated that the Independent Curriculum, although new, had positive and negative aspects. Many feel that this curriculum is more practical than the previous curriculum, although it still requires further in-depth study. 2). The main obstacle faced is the difference in concentration and catching speed of students. Some students are able to follow learning quickly, while others lag behind, similar to problems that existed in the previous curriculum. 3). Teachers provide remediation for students with low IQs or who are behind their peers. This approach helps students focus on learning according to their individual needs. 4). Students have become more creative and independent since the implementation of the Merdeka Curriculum, which encourages them to be more active in the learning process. 5). The Merdeka Curriculum focuses more on student activities, while in the 2013 Curriculum (K13) teachers play a greater role in explaining and analyzing material before students start working.